Pengaruh Knowledge Management Dan Kompetensi Terhadap Daya Saing Global Bisnis Perhotelan: Peran Moderasi Kinerja - Fendy Kurniawan; Welli Braham Kurniawan (AKPARDA, 2025)
The growth of the hospitality industry without the accompanying knowledge of good management and business sustainability is highly uncertain due to limited internal resources, limited access, competition, and increasingly stringent technology with new applications. It is very important for hospitality businesses to maintain their business continuity. Research shows that knowledge management has a significant positive effect on hospitality management performance in the international arena, meaning that the higher the level of knowledge management in the international arena, the better the competitiveness. Competence has a significant positive effect on the competitiveness of hotels in the international world, meaning that the higher the competence built in hotels, the better the competitiveness in making final decisions to create internationally competitive hotels. Improvements in organizational performance moderate the influence of knowledge management on the competitiveness of hotels in the international arena, meaning that the better the improvement in organizational performance, the greater the increase in knowledge management on competitiveness in hotels in the international arena. Improved organizational performance moderates the influence of competency on the competitiveness of the hospitality industry in the international arena, meaning that the better the improvement in organizational performance, the greater the impact on competency in terms of competitiveness in the hospitality industry in the international arena.